Dynamized high dilutions for management of the leafcutter ant Acromyrmex laticeps Emery (Hymenoptera: Formicidae) (Acta Scientiarum. Agronomy, 2017)
High dilutions may have different biological effects due to the dynamization method and the dilution order used. The aim of this paper was to evaluate the foraging activity of the leafcutter ant Acromyrmex laticeps subjected to high dilution preparations originating from grinding worker ants and developing dilutions at the following dynamizations: 6, 12, and 30 CH (centesimal Hahnemannian dilution order), 5 LM (fifty millesimal Hahnemannian dilution order) and 35 K (Korsakovian dilution order). The preparations were applied daily for 10 days by spraying them on moving ants on tracks close to the anthill. The evaluations included counting the number of ants transporting vegetable fragments on the tracks before each application, after application, and 20 and 30 days after the first application. The high dilution preparations for the 6 and 30 CH and 35 K treatments reduced the foraging activity of the leafcutter ant A. laticeps after 10 applications. The 30 CH treatment showed a higher reduction in the foraging activity of A. laticeps anthills. Prolonged reduction of the foraging activity of A. laticeps anthills was observed 20 days after the first application with the 35 K and 30 CH treatments.